The Desocialising of Economic Theory - William A. Jackson (International Journal of Social Economics, 2013)
This paper aims to show that economic theory has become `desocialised' and separated from social theory through the adoption of individualistic methods and neglect of social relations and structures. A historical overview traces how the social content of economic theory has diminished, considering the reasons why. Desocialisation has stemmed from the desire for boundaries between academic disciplines, which drove economics towards individualism and other social sciences towards structural methods. Such an artificial divide between economic theory and social theory is argued to be detrimental to all the disciplines concerned. Restrictions imposed by desocialised theory have practical consequences for how we understand and model the economy. Some reforms that would loosen the restrictions so as to promote a resocialised economics are suggested.
Keywords: B40; B50; Z10; 330; economic theory; social theory; methodological individualism; social structure; duality; stratification